Konut kooperatif yapılarında görülen hasar ve kusurların kooperatiflerin yapısal özellikleri bakımından irdelenmesine ilişkin bir model önerisi 1980 sonrası Konya örneği - Koç, İlhan (Fen Bilimleri Enstitüsü, 2000)
Sosyal, kültürel ve siyasal yapısı gereği, 1950'lerden beri hızla artan nüfusu ile Türkiye, bütün sektörlerde hızla gelişti ve büyüdü; ve böylece günümüze kadar yoğunlaşarak devam eden şehirleşme süreci sebebiyle ortaya çıkan konut açığı, ülkede kuşkusuz günümüzün en önemli sorunlarından birini teşkil etmektedir. Bu yüzden, konut sorununa ilişkin tespitler yapmak, bunlara çözümler geliştirmek ve yönlendirici bilgiler üretebilmek için, her zaman teorik ve uygulamalı araştırmalara ihtiyaç vardır. Bu araştırmalar, ülke, il ve bölge ölçeğinde olabileceği gibi, şehir ölçeğinde de çalışmalar yapılarak da gerçekleştirilebilir. Ülke genelinde 1980'lere kadar bilimsel planlamadan yoksun olarak devam eden geleneksel konut yapı kooperatifçiliği yolu ile sağlanan konut edinme, 1980'lerin ilk yıllarından itibaren başta dar gelirli kesim olmak üzere toplumun diğer bütün kesimleri tarafından başvurulan en önemli bir yöntem olmuştur. Bu durum, özellikle 1981 ve 1984 tarihli Toplu Konut Kanunları'nın sağladığı iyileştirmeler ile birlikte ekonomi ve yapım sektöründeki büyük gelişmeler ile desteklenmiştir. Fakat, planlama, yapım ve kullanım bakımından olumlu yönleri yanı sıra, kuşkusuz bir çok ; olumsuzlukları da beraberinde getirmiştir. 'h Bu çalışmada, çok yoğun bir kooperatifçiliğin yaşandığı 1980 sonrası dönemde, ülke ^ geneline göre konut yapı kooperatifçiliğinde çok önemli bir yeri olan Konya'daki konut kooperatif yapılarda görülen yapı hasar ve kusurların nedenleri, kooperatiflerin yapısal özellikleri ve konutlarının kullanımı bakımından değerlendirilmektedir. Çalışmanın birinci bölümü olan giriş kısmında, çalışmanın amacı, kapsamı ve hedefleri; aşamaları, verileri, araştırma metodu ve konu ile ilgili daha önce yayınlanmış çalışmalara değinilmektedir. İkinci bölümde, Konya'nın çevresel verileri, şehirsel planlama süreci, ve konut planlaması konularına kısaca değinilmektir. Burada, şehrin kısa tarihçesi, coğrafi, iklim ve atmosferik özellikleri ile demografik yapısı, nüfus hareketi ve istihdam özellikleri açıklandıktan sonra şehirsel planlama süreci ve konut planlaması konularında kısa bilgiler verilmektedir. Üçüncü bölümde, kooperatifçilik kavramına girilmekte ve konut kooperatifçiliğinin Türkiye'de ve Konya'daki gelişim süreci incelenmektedir. Burada, özellikle çalışma alanı olarak seçilen Konya'da genelde kooperatifçilik ve konut kooperatifçiliğinin gelişimi ve mevcut durumu hakkında detaylı bilgi verilmektedir. Bu tezin alan çalışmasının büyük bir kısmını içeren dördüncü bölümünde ise, Konya'da 1980'den sonra kurulmuş ve kullanılmaya başlanmış (yapı kullanma izni alınmış) olup ta tasfiye olmuş ve/veya kısmen devam etmekte olan konut yapı xvi kooperatifleri hakkında yapılan anket sonuçlan detaylı olarak incelenmektedir. Bu kısımda, Konya'nın çeşitli bölgelerinden seçilmiş değişik büyüklük ve nitelikteki 150 adet kooperatifin oluşumları, yönetimi, ortakları ve de konutlarının kullanıcıları hakkında genel bilgilerin yanı sıra; kooperatif yapılarının ve konutlarının fiziki durumlarına ilişkin olarak, genelde insan hatalarıyla oluşmuş bir takım hasar ve kusurlar sonucunda yapılmış veya yapılması gerekli olan önemli tamir veya değişikliklerine ait tespit edilen anket sonuçları kapsamlı olarak ortaya konmakta ve irdelenmektedir. Beşinci bölüm de, yine alan çalışmasının büyük bir kısmını oluşturmaktadır. Başlangıçta, yapı hasar ve kusuru tanımı, çeşitleri ve bunlara sebep olan etkenler ve kaynakları genel olarak sunulmaktadır. Daha sonra, kooperatif yapılarında kullanılan malzemeler, yapım teknikleri ve tespit edilen hasarlar, kusurlar ve bunların sebeplerine ilişkin etkenler ve kaynaklan, yapı alt sistemine bağlı yapı elemanlarına göre incelenmektedir. Bu etken ve kaynaklar, daha çok insan hatalarından kaynaklanan yanlış tasarım ve yapım süreci, yanlış malzeme seçimi ve uygulama, kötü işçilik ile birlikte yanlış bina kullanımı, bina bakım kusurlarına ilişkin faktörlerle açıklanmaktadır. Ayrıca, doğal olaylar ve diğer dış faktörler, yapı yükleri ve malzemelerin kendinden kaynaklanan sebeplere ilişkin faktörlere de kısaca yer verilmektedir. Altıncı bölümde, saha çalışması sonucu ortaya konan anket sayısal sonuçlarının, bu çalışmanın amacı doğrultusunda değerlendirilerek irdelenmesi ile bir model önerisi yapılmasına çalışılmaktadır. Önce, kooperatif yapılarında hasar ve kusurların oluşumunda etkili olan faktörler kısaca belirlenmekte, daha sonra, kooperatif yapılarında tespit edilen yapı hasar ve kusurların, oluşumlarında etkili olan faktörler bakımından irdelenmesi anket sonuçları yardımı ile detaylı olarak yapılmaktadır. Son kısmında ise, yapı hasar ve kusurlarının oluşumunda etken olan kooperatif yapısal özellikleri ve diğer faktörlere ilişkin bir model önerisi sunulmaktadır. Yedinci ve son bölümde ise, tezin özellikle alan çalışmasına ait bölümleri başta olmak üzere, ortaya konan bilgiler sonuçlan bakımından kısaca değerlendirmekte ve gerekli çözüm önerileri ortaya konmakta ve tartışılmaktadır. Şöyle ki; özellikle, dar gelirli ailelerin bir araya gelerek ucuz konut sahibi olmak için kurdukları konut yapı kooperatifleri genelde bu işlevlerini sürdürmekte iseler de, söz konusu Toplu Konut Kanunlarının sağladığı iyileştirmelerden vazgeçilmesiyle, ve de özellikle 1990'ların başından itibaren ülkenin ekonomisinin ağırlaşan şartları bu fonksiyonlarını yavaşlatmış, ve böylece konut kooperatifçiliği artık ticari bir organizasyon haline dönüşmeye başlamıştır. Bu yüzden, bu durumun kooperatif yapılarının genel kalitesine, mimari ve yapım tekniğine olumsuz olarak etki yaptığı görülmüştür. Bunu önlemek için, kooperatifler, yasal yollar ve özellikle kendi özdenetimi ile çok daha sıkı bir denetleme metoduyla asli işlevlerine döndürülmeye zorlanmalıdır. Bu sebeple, kooperatifçikle ilgili olarak resmi veya özel yeni kurumsallaşmalara gidilmesi gerekmektedir. Yine, yapımın belirlenen süre içinde ciddiyetle tamamlanması için, kooperatif yönetimleri, başlangıçta doğru planlama ve projelendirme ile birlikte kaliteli ve ucuz malzeme ve de kalifiye işçilik temin etmelidir. Ayrıca, mevcut kaynakların daha rasyonel kullanılabilmesi için, hızlı yapı üretimini sağlayan endüstrileşmiş yapım teknikleri ve modern malzemeler gündeme girmelidir.

As a result of its social, cultural and even political composition, Turkey, with an increasing population since 1950s, has developed and grown in all sectors fast; therefore, the housing shortage occurred due to the continuous urbanization development to present day extensively, is certainly one of the most important problems of today in the country. That is why, in order to establish the housing problems, to develop solutions and to produce orienting knowledge for them, the theoretical and applied researches are always necessary. These investigations may be carried out by the studies in the scale of a city, as well as in the scale of entire country, a county or a region. Owning a house provided by means of housing co-operatives, which in the generality of the country up to 1980s were retainig as a traditional concept without any scientific planning, has become the most significant method that is required by all sections of the society, especially the low-income ones from the first yeras of 1980s onwards. It was especially supported by the great developments in economy and building construction sectors together with the improvements contributed by the Mass Housing Act of 1981 and 1984. However, besides its positive aspects in terms of planning, construction and usage, without doubt it has got brought a great deal of negative aspects, as well. In this study, within the period of after 1980 in which a very intensive housing co operatives have been experienced in the country, the causes of buildings failures and defects, which were obsereved on the buildings of the housing co-operatives in Konya that has got a very important place in the housing co-operatives compare to the generality of the country, are examined in terms of the framework characteristics and the usage of houses (flats) of housing co-operatives. In the introduction section which is the first chapter of the thesis, the aim, the boundaries and the objectives of the study, such as its stages, data, investigation method and the source^ related to the subject issued previously, are dealt with. In the second chapter, the environmental aspects of Konya, its urban planning progression and the subjects of housing planning, are dealt with briefly. Here, after explaining the short history of the city, its geography, climate and atmospheric characteristics together with its demographic structure, population movement and employment characteristics; short information are presented about the subjects of urban planning progression and housing planning of the city. XVlll In the third chapter of the thesis, the co-operative concept is introduced, and the development progression of the housing co-operatives in Turkey and in Konya, is investigated. In this section, some information especially about the development and present situation of co-operative in general and housing co-operative in Konya which is selected as a fieldwork area for the study, is given in detail. In the fourth chapter which also contains the majority part of the fieldwork, the questionaire results carried out about the housing co-operatives, which were established in Konya after 1980, and as their buildings began to be used (provided the building usage permission), were liquidated and/or have been partly continuing, are investigated in detail. In this section, besides general information concerning the establishment, the management, the members and also the users of 150 housing co operatives in different size and quality selected from various regions of Konya, the questionaire results determined for the important repairs or changes which have been carried out or must be carried out in near fiiture, as a result of some buildings failures and defects caused by human faults related to the physical conditions of the buildings and the houses (flats) of housing co-operatives, are put forward and scrutinized extensively. The fifth chapter also comprises the main section of the fieldworks. At the beginning, the definitions of building failures and defects, their types, and the factors and the sources causing them, are presented. Then, according to the building elements belonging to building sub-system, the building materials used in the co-operative buildings, their building techniques and the building failures, the defects surveyed and the factors and the sources related to their causes, are examined. These factors and sources are explained with the factors caused by human faults that are imperfect design and building process, wrong material selection and application, and bad craftsmenship, together with the factors related to the faulty building usage and building maintenance defects. In addition, the factors related to the causes originated from natural events and other external factors, building loads and the internal actions of materials, are dealt with shortly. In the sixth chapter, it is tried a model suggestion by examining the result of the field works carried out with an qeustionaire in the direction of the study. A model is introduced related to the effective characteristics of co-operatives buildings and the other factors in the formation of the building failures and defects The seventh chapter concluding the study, evaluates briefly especially the fieldwork sections of the thesis, and the knowledge presented concerning the results, and finally puts forward some necassary recommendations. That is to say, even the original function of housing co-operatives established by the low-income families by coming together to own cheap houses, have been continuing in general; because the rejection of improvements provided by the Mass Housing Laws, and also especially the recession of the country's economy since the beginning of 1990s made their original function to slow down, and so the housing co operatives have begun to be a financial organisation to earn money. Therefore, it was determined that this situation has affected the general quality of co-operative buildings, their architecture and structural techniques negatively. In order to prevent this, with a firm controlling method, legal ways and/or especially self-controlled, the housing co-operatives must be forced to turn to their original function. For this reason, as concerning the housing co-operative, to establish new official or private XIX institutions are necessary. Furthermore, in order to complete building construction seriously within the determined period, co-operative managements should provide at first right planning and projects, and quality and cheap building materials and also qualified craftsmenship. Moreover, in order to use the existing sources more rational, industrialized building techniques providing fast building production, and modern building materials should be put on agenda.
A Model suggestion related to the examination of building failures and defects observed on the buildings of housing cooperative, in terms of their framework characteristics; A case study of Konya after 1980
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2000
Thesis (Ph.D.) -- İstanbul Technical University, Institute of Science and Technology, 2000
Keywords: Bina bilgisi; Hasar; Konut kooperatifleri; Yapı malzemeleri; Building information; Damage; Housing cooperatives; Building materials